2008 11th International IEEE Conference on Intelligent Transportation Systems 2008
DOI: 10.1109/itsc.2008.4732566
|View full text |Cite
|
Sign up to set email alerts
|

Stereovision-based 3D lane detection system: a model driven approach

Abstract: A new stereovision-based method for the road lane detection and 3D geometry estimation is presented in this paper. The proposed approach is based on a recognition algorithm driven by a statistical model of the 3D road lane, projected in both stereoscopic images. First, the model is initialized thanks to a training stage. The model is then updated iteratively, from successively extracted image features. After each iteration, the detection of the next features, in any of the two images of the stereoscopic pair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…The lane detection and tracking is performed using single camera while the obstacle detection is carried out based on stereo vision. In [35], a 3D lane detection method is given based on stereo vision, where the parameters of the 3D lane, such as width, horizontal and vertical curvature, roll, pitch, and yaw angles, are estimated. Similarly, Nedevschi et al propose a stereo vision based lane detection and tracking scheme, where the lane is modeled as a 3D surface, defined by the vertical and horizontal clothoid curves, the lane width and the roll angle.…”
Section: Related Workmentioning
confidence: 99%
“…The lane detection and tracking is performed using single camera while the obstacle detection is carried out based on stereo vision. In [35], a 3D lane detection method is given based on stereo vision, where the parameters of the 3D lane, such as width, horizontal and vertical curvature, roll, pitch, and yaw angles, are estimated. Similarly, Nedevschi et al propose a stereo vision based lane detection and tracking scheme, where the lane is modeled as a 3D surface, defined by the vertical and horizontal clothoid curves, the lane width and the roll angle.…”
Section: Related Workmentioning
confidence: 99%
“…In this chapter, we only concentrate on the 2D models which assume a flat road plane. Detailed studies of 3D models can be found in [2,8,23].…”
Section: Lane Modellingmentioning
confidence: 99%
“…A lane detection component that is based on contextual cues was developed in [12]. There are also stereovision based approaches that extend the 2D road model to the 3D world [13].…”
Section: Introductionmentioning
confidence: 99%